UPAYA PENYULUH PERTANIAN DALAM PENERAPAN TEKNOLOGI IRIGASI TETES (DRIP IRRIGATION) KABUPATEN BANYUASIN (STUDI KASUS KELOMPOK TANI RUKUN MAKMUR DESA BUDI MULYA KECAMATAN AIR KUMBANG) Agricultural Development Effort in Irrigation Technology Implementation (Drip Irrigation) Banyuasin District (Case Study of Rukun Makmur farmer Group Budi Mulya Village Air Kumbang Regency) - Andrian, Andrian; H. Anang, Rahidin; Kurniawan, Rahmat (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
The purpose of this research is to know Agricultural counselor effort to convince farmer group in applying drip irrigation technology in Regency of Banyuasin And the obstacles of farmer in applying drip irrigation technology in Regency of Banyuasin. This research was conducted in the Budi Mulya Village of the district Air Kumbang Banyuasin Regency. In March until May 2017. The research method used is case study method. The sampling method that used in this research are purposive sampling and systematic sampling. Data methods of collection used in this study are observation and interviews directly to the respondents who have been determined using the tools of quisionary aids that have been prepared previously and documentation and secondary data. Data processing is done using descriptive-qualitative method. The results of the study showed that the efforts of Agricultural counselor in applying drip irrigation technology include: drip irrigation technology socialization, selection of extension method, the procedures for the use of drip irrigation, the application of drip irrigation. And obstacles faced by farmers in the process of applying drip irrigation technology is a problem: capital for the purchase of equipment for drip irrigation such as drip hoses and Water source caused the dry season farmers getting difficulty water supply to watering and fertilizing plants.